The importance of good health and well-being in Sekarkare Village, Probolinggo, East Java Village, Probolinggo, East Java - Kuntjoro, Mefina; Hendrijantini, Nike; Safari Azhar, Imam; Ayu Nararya, Sheila; Danang Subeqi, mochamad (Faculty of Dental Medicine Universitas Airlangga, 2024)
Background: Oral health is essential to total health and a satisfactory quality of life. One of the most contributingfactors is how a human being has an understanding of how to maintain oral health to improve the quality and well-being of life. Purpose: to provide and describe the community knowledge about the importance of replacing missing teeth using dentures and maintaining oral health to improve the quality of life. Methods: The event was carried out with an interactive educational concept by giving pre- and post-tests at the beginning and end of the event. There were at least 80 education participants, consisting of the people of Sekarkare village of various ages, from late adolescents to the elderly, along with village officials and guests from the Sekarkare Health Center. The activity was carried out at the village hallof Sekarkare Village, Dringu District, Probolinggo Regency, East Java. Results: The majority of people understand and are enthusiastic about participating in a series of counseling events. There is an increase in scores in the pre-test (59,06%) and post-test (65,58%) results. Conclusion: The existence of counseling events with interactive educational concepts can increase public enthusiasm for participating in events, making it easier for people to gain new knowledge.